Colorless polyimide films with low birefringence and retardation: Synthesis and characterization. (16th January 2023) - Li, Xiaohong; Wang, Minyan; Mushtaq, Nafeesa; Chen, Guofei; Li, Guohua; Fang, Xingzhong; Zhang, Anjiang
Abstract: In this study, two series of polyimides (PI) were synthesized from one step solution polycondensation of two diamines containing sulphonyl group with aromatic and aliphatic dianhydrides. These PIs showed good organosolubility and were casted into films with high transparency of T 500 >86%, and cutoff wavelength in the range of 295–370 nm. Optical birefringence (0.0020–0.0127) of these PIs was lower than that of traditional aromatic PI. PI films demonstrated out-of-plane retardation ( R th ) in the range of 42–279 nm, indicating low optical anisotropy of these films. All PIs also exhibited high thermal stability with glass transition temperatures ranging from 200 to 339 °C. PI-1c derived from bis[4-(3-aminophenoxy)phenyl] sulfone ( m -BAPS) and 4, 4′-(4, 4′-isopropylidenediphenoxy)bis(phthalic anhydride) (BPADA) showed the lowest birefringence and good transparency. Graphical abstract: Image 1 Highlights: Synthesis of two series of transparent PI films with low birefringence and retardation. Role investigation of ether and SO2 groups of two diamines on polymer film properties. PI-1c with T 500 of 87% showed the lowest birefringence of 0.0020 and Rth of 42 nm.